Modernisme Islam dan Perkembangan Intelektualisme Islam - Satibi; Maman Rahman Hakim; Muhamad Rezi (Al Ashriyyah, 2023)
Islam is a religion that contains universal teachings. Some things are given relatively detailed descriptions, but some big things are left universal. Such as state, social, economic, and cultural orders whose values ​​are universal. Nevertheless, Islamic principles form the basis for making ijtihad on the details of these aspects. This article describes the phenomenon of Islamic modernism and the development of Islamic intellectuality, especially in Indonesia.